Pemimpin Kampung Tunagrahita - Insyira Yusdiawan Azhar; Kushandajani Kushandajani; Andriani Gita Swela (Universitas Medan Area, 2019)
This research will discuss the leadership pattern of Eko Mulyadi as the head village in empowering Tunagrahita people in an area known as Tunagrahita Village. Eko Mulyadi is considered successful in empowering people who have an impact on the lives of people with intellectual disabilities. According to the research of Putri and Haryanti (2017), Eko's success cannot be separated from the four characteristics of transformational leadership. However, the research has a theoretical gap because of the limited scope of Bass and Riggio's leadership who are unable to review the process of the leader approach to his followers. So there is a gap that results in the weakness of the theory to explain how the relationship between the leader and true followers. The purpose of this research focuses on the process and dynamics, as well as what contextual values are intertwined between Eko Mulyadi as a leader and people with intellectual disabilities so that they can successfully transform. This study uses a qualitative ethnographic method that is carried out for three weeks in the field with data collection techniques through observation and interviews. The results of this research indicate that the communication style, trust, reframing of the head village towards Tunagrahita, and full attention are the keys to the success of empowerment.